1954
DOI: 10.1037/h0061454
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up after three years of clients counseled by two methods.

Abstract: These scores were computed by the present authors from summed responses to multiple-choice questions In the 1949 evaluation interview.tained in the present follow-up do not differ significantly from zero. The only correlations of any magnitude are those between objective and rated measures of attitude. These are moderately high when the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1957
1957
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…DISCUSSION These data are compatible with the hypothesis that nondirective therapist behavior influences college students toward perceiving a therapist as being more understanding, having a higher level of regard for his patient, and being less conditional in his regard for his patient than does directive therapist behavior. These results are consistent with the preference for nondirective therapists reported by Barahal et al (1950), but tend to contradict results from those studies in which subjects indicated that they prefer directive therapist behavior (Forgy & Black, 1954;Grigg & Goodstein, 1957;Sonne & Goldman, 1957). It is of interest that nondirective therapist behavior seems to elicit favorable perceptions along three of these dimensions, since they have been found to be related to patients' progress in therapy.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…DISCUSSION These data are compatible with the hypothesis that nondirective therapist behavior influences college students toward perceiving a therapist as being more understanding, having a higher level of regard for his patient, and being less conditional in his regard for his patient than does directive therapist behavior. These results are consistent with the preference for nondirective therapists reported by Barahal et al (1950), but tend to contradict results from those studies in which subjects indicated that they prefer directive therapist behavior (Forgy & Black, 1954;Grigg & Goodstein, 1957;Sonne & Goldman, 1957). It is of interest that nondirective therapist behavior seems to elicit favorable perceptions along three of these dimensions, since they have been found to be related to patients' progress in therapy.…”
Section: Resultssupporting
confidence: 65%
“…The directive-nondirective continuum was selected because of its earlier identification with the client-centered approach (Rogers, 1942) and the controversy which resulted when other therapists indicated that they, too, use nondirective techniques under certain conditions (e.g., Seeman, 1965). Studies focusing on psychotherapy patients' and vocational counseling clients' preferences for therapists along this continuum have produced generally contradictory results (Ashby, Ford, Guerney, & Guerney, 1957;Barahal, Brammar, & Shostrom, 1950;Forgy & Black, 1954;Grigg & Goodstein, 1957;Sonne & Goldman, 1957).…”
Section: Veterans Administration Hospital Brockton Massachusettsmentioning
confidence: 99%
“…These are variables involved in the interpersonal relationship between client and therapist" (1959, p. 57) . Clients' reports of counselor variables have b een utilized by Arbuckle (1956), Forgy and Black (1954 ), Snyder (1957 ) and in the above cited study by Grigg and Goodstein. Certainly since studies find that one cannot predict counselor responses by the theoretical orientation subscribed by the counselor Strupp, , 1957Wrenn, 1960), it is imperative to obtain some report of observations of counselors during the interview hour.…”
mentioning
confidence: 99%
“…After considering their self-evaluation history, and Bixler (1946) and Kirk (1969) recommended that counselors encourage client participation in selecting appropriate tests. At one time, the issue of whether counselors or clients should select tests was considered quite controversial and led to several research studies (Forgy & Black, 1954;Gustad & Tuma, 1957;Seeman, 1948Seeman, , 1949. This issue was for the most part a "strawman" about humanism and authoritarianism over which directivists and nondirectivists argued.…”
Section: About How Clients Combine Test Data and Other Information Tomentioning
confidence: 99%